NDC : The Generic Old-Age Pension Scheme - Góra, Marek; Palmer, Edward (World Bank, Washington, DC, 2019)
This paper defines a universal public pension scheme (UPPS) as a government mandated lifecycle longevity insurance scheme that transfers individual consumption from the working years to retirement. It discusses the differences in four UPPS designs designated as either defined contribution (DC) or defined benefit (DB), and financial or nonfinancial. With individual DC accounts, the ball is in the individual’s court. The transparent link between contributions and retirement income is the enabler of efficiency that through marginal decisions to choose formal work over informal work or leisure and to postpone retirement marginally toward the end of the working life, supports affordability and sustainability for a chosen level of adequacy. Hence, UPPS-DC designs are found superior to UPPS-DB designs.